Solve for b -90=-5(-3b)

Math
-90=-5(-3b)
Rewrite the equation as -5(-3b)=-90.
-5(-3b)=-90
Multiply -3 by -5.
15b=-90
Divide each term by 15 and simplify.
Tap for more steps…
Divide each term in 15b=-90 by 15.
15b15=-9015
Cancel the common factor of 15.
Tap for more steps…
Cancel the common factor.
15b15=-9015
Divide b by 1.
b=-9015
b=-9015
Divide -90 by 15.
b=-6
b=-6
Solve for b -90=-5(-3b)

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top